2005
DOI: 10.1136/jnnp.2004.055657
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities as a predictor of neuropsychological deficits post-stroke

Abstract: Objectives: Cerebral white matter hyperintensities (WMHs) on magnetic resonance imaging (MRI) are a recognised risk factor for post-stroke dementia. Their specific relations to cognitive impairment are still not well known. The purpose of this study was to explore how the severity and location of WMHs predict neuropsychological test performance in the context of other brain lesions in elderly stroke patients. Methods: In the Helsinki Stroke Aging Memory Study, 323 patients, aged from 55 to 85 years, completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 41 publications
5
105
2
1
Order By: Relevance
“…36,37 Although leukoaraiosis was associated with CDF and correlated with cognitive tests in this study, it was not a predictor, presumably because of the low frequency of leukoaraiosis. Again, this could be explained by the low age and high MMSE of our patients.…”
Section: Discussionmentioning
confidence: 67%
“…36,37 Although leukoaraiosis was associated with CDF and correlated with cognitive tests in this study, it was not a predictor, presumably because of the low frequency of leukoaraiosis. Again, this could be explained by the low age and high MMSE of our patients.…”
Section: Discussionmentioning
confidence: 67%
“…Extent of poststroke recovery varies with many patient-related factors (e.g., age at stroke onset, sex, handedness, socioeconomic status) and various stroke-and lesion-related factors (e.g., initial stroke severity, lesion size, stroke subtype, lesion location), but these factors have very limited predictive power for outcome (19)(20)(21)(22)(23)(24). Even good predictors, including initial stroke severity and lesion volume, leave most of the variability in outcome unexplained (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…This line of research followed from the observations that, according to some authors, there are differences between the neuropsychological patterns of DAT patients and those of patients with VD resulting from small-vessel disease. The former consistently show a predominance of episodic memory disorders (Gainotti et al, 1989(Gainotti et al, , 2001Graham et al, 2004;Ingles et al, 2007;Looi & Sachdev, 1999;Matsuda et al, 1998;Mendez &Ashla-Mendez, 1991), whereas the latter appear to show a prevalence of executive dysfunction (Desmond, 2004;Jokinen et al, 2005;Kertesz & Clydesdale, 1994;Kramer et al, 2002;Looi & Sachdev, 1999;Padovani et al, 1995). Furthermore, psychomotor retardation, considered to be a prominent consequence of stroke (Ballard et al, 2003;Rasquin et al, 2004) is also found in small-vessel subcortical dementia (Gainotti et al, 2001), in vascular cognitive impairment (Desmond, 2004) and in association with recognized risk factors for vascular dementia, such as white matter hyperintensities (Jokinen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The former consistently show a predominance of episodic memory disorders (Gainotti et al, 1989(Gainotti et al, , 2001Graham et al, 2004;Ingles et al, 2007;Looi & Sachdev, 1999;Matsuda et al, 1998;Mendez &Ashla-Mendez, 1991), whereas the latter appear to show a prevalence of executive dysfunction (Desmond, 2004;Jokinen et al, 2005;Kertesz & Clydesdale, 1994;Kramer et al, 2002;Looi & Sachdev, 1999;Padovani et al, 1995). Furthermore, psychomotor retardation, considered to be a prominent consequence of stroke (Ballard et al, 2003;Rasquin et al, 2004) is also found in small-vessel subcortical dementia (Gainotti et al, 2001), in vascular cognitive impairment (Desmond, 2004) and in association with recognized risk factors for vascular dementia, such as white matter hyperintensities (Jokinen et al, 2005). A further difference between DAT and VD could include phonological and semantic fluency, because some authors (e.g., Canning et al, 2004;Jones et al, 2006), but not others (e.g., Bentham et al, 1997;Crossley et al, 1997) have found a greater semantic fluency impairment in DAT patients and a greater phonological fluency impairment in VD patients.…”
Section: Introductionmentioning
confidence: 99%